The Relationship Between Consumer Values, Needs and Purchase Behavior of Men’s Facial Skin Care Products in Malaysia Based on Gender - Ding, Xiao Qin (2006)
The cosmetic market has been cornered by women for a long time. People also consider that beauty is a necessary part of women’s life. However, time has changed. Men in modern society around the world are starting to jump into the cosmetic market and showing an increasing interest in their physical appearance as seen by the growing trend of consuming self-care and fashion products in order to enhance the way they look in recent years. Due to a lack of research studies on the increasing potential of the men’s personal care market, with focus on facial skin care products, the study on the relationship between personal values, needs and purchase behavior of Men’s facial skin care products in Malaysia has been conducted. Within a multi-racial country such as Malaysia, how both female and male view the men’s facial skin care based on the kind of values, needs and purchase behavior and why people purchase men’s facial skin care products are looked into for this study. The results suggest that values and needs do influence the behavior of consumers for men’s facial skin care purchasing. Moreover, the results also suggest ways that cosmetic companies can improve their market strategies and channels of advertisement for the men’s facial skin care products market. Besides that, marketers can further aid on the cosmetic knowledge of male consumers in Malaysia in future.